2023
DOI: 10.1159/000529084
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Challenge-Proven Beta-Lactam Allergy in Children with Immediate and Non-Immediate Mild Cutaneous Reactions

Abstract: <b><i>Introduction:</i></b> Beta-lactam (BL) antibiotics are the most often involved drugs in allergic reactions. Mild cutaneous reactions such as maculopapular exanthema or urticaria are the most common presenting complaints of BL allergy in the pediatric population. However, it can be challenging to distinguish BL-induced allergy from reactions due to infections or other reasons. In this study, we aimed to determine the clinical characteristics and potential risk factors of true BL al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
4
1
Order By: Relevance
“…Female sex, the age at the time of the possible allergic reaction, a history of allergy to other antibiotics, atopic dermatitis, and rhinitis have been identified as risk factors in some studies, while others found no correlation [43][44][45][46][47][48]. In our study we did not observe a correlation between these factors and an increased risk of positive allergic testing.…”
Section: Discussioncontrasting
confidence: 71%
“…Female sex, the age at the time of the possible allergic reaction, a history of allergy to other antibiotics, atopic dermatitis, and rhinitis have been identified as risk factors in some studies, while others found no correlation [43][44][45][46][47][48]. In our study we did not observe a correlation between these factors and an increased risk of positive allergic testing.…”
Section: Discussioncontrasting
confidence: 71%
“…Previous studies have reported an association between atopic diseases and IRs to BLs (60, 61). However, other studies have not found evidences to support that allergologic background such as atopy, elevated specific IgE levels, or rhinitis increase the risk of developing an allergic reaction to BLs (2,(62)(63)(64).…”
Section: Immunochemistry and Mechanisms Involved In Bl Allergymentioning
confidence: 97%
“…Several authors have observed a higher proportion of confirmed BL allergy in children reporting IRs compared with those experiencing NIRs ( 2 , 62 , 67 , 68 ). However, others could not find any correlation between BL allergy and the timing of reactions ( 64 ). Indeed, it has been reported that up to 17% of children reporting NIRs were confirmed as allergic by experiencing an IR in DPT ( 2 , 3 , 54 , 57 , 59 , 68 73 ).…”
Section: The Value Of Clinical Historymentioning
confidence: 99%
“…Children have less exposure to drugs, and maculopapular exanthems due to acute infections are more common [ 89 ]. Sipahi Cimen et al [ 116 ] have evaluated 214 children with suspected mild cutaneous reactions to BLs in a 5-years period. BL allergy was diagnosed by oral provocation test in 10.7% of children.…”
Section: Risk Factors Related To the Hostmentioning
confidence: 99%